Successful surgical correction of ventral hysterocele in a goat - MURUGAVEL, K; ALPHONSE, R M D; ANTOINE, D; RAJU, M S (The Indian Journal of Animal Reproduction, 2002)
A successful surgical correction of left side unilateral ventral hysterocele in a goat and its subsequent successful conception and parturition is reported.